EKONOMI SYARIAH: ALTERNATIF SISTEM EKONOMI MENUJU KESEJAHTERAAN YANG ADIL DAN BERKELANJUTAN - Imtinan, Hana; Septiani, Dewi; Wijaya, Icha Trina; Sajjed, Jiwa; Simamora, Audra Syachriar (Pusat Riset dan Publikasi, 2024)
Sharia economics is an economic system that implements the basic values ??and principles of sharia, derived from Islamic teachings, the values ??and principles of sharia are universally applicable in all aspects of life, including economic and financial activities. Sharia economics based on Islamic values ??offers an alternative economic system that is just, prosperous, and sustainable. Its principles, such as monotheism, justice, and halal, aim to achieve falah and build a prosperous society. Its benefits include economic stability, reducing inequality, and moral values ??in economic activities. This study used a qualitative method with a literature study approach. The used of literature studies in this research aims to gain deeper insight into the concept of Islamic economics as an alternative to a fair and sustainable economic system. The results of this study indicate that sharia economics is an alternative economic system that promises to achieve just and sustainable prosperity. The rapid development of sharia economics in Indonesia is marked by the establishment of various sharia financial institutions and increasing public awareness. Career opportunities are wide open in various fields, such as sharia banking, sharia insurance, and sharia economic education. Islamic economics has great potential to be a solution to economic problems in Indonesia and the world.